Voices of Resilience: Women Protagonists in Indian Literature and Their Journey towards Empowerment - Snehal A. Rahane, Dr. Mohini R. Gurav (Journal of Informatics Education and Research, 2025)
"Voices of Resilience: Women Protagonists in Indian Literature and Their Journey Towards Empowerment" explores the portrayal of women's resilience and empowerment through key female protagonists in Indian literature. The paper examines a range of literary works spanning different regions, languages, and historical periods to highlight how these characters challenge societal norms, navigate patriarchal structures, and assert their identities. Through a comparative analysis of novels, short stories, and poetry, this study sheds light on themes of resistance, self-discovery, and transformation. It argues that these narratives not only reflect the evolving role of women in Indian society but also inspire broader conversations about gender equality and social justice. By situating these stories within their cultural and socio-political contexts, the paper underscores the significance of literature in fostering women's empowerment and resilience.